CONSTRUCTION 5.0 IS ON THE WAY TO BECOMING THE STRONGEST INDUSTRY THAT ADVANCES SOCIAL SUSTAINABILITY IN THE DIGITAL AGE. A MATURITY ASSESSMENT - Weber-Lewerenz, Bianca (International Journal of Engineering Science Technologies, 2025)
Convincing use cases and reliable empirical values are essential for the construction industry and its decision-makers to face the questions and challenges of digital transformation and to shape their own digital strategy. In fact, a connection has been identified between the increasing acceptance of digitization in construction companies and the innovative creation of use cases. Therefore, the aim of this study is to examine the evidence that will greatly facilitate the development of such an innovation scenario and ensure even wider adoption. The study critically questions whether the perception of the construction industry as one that is lagging behind digitization and Artificial Intelligence (AI) is realistic or not, or whether the industry is rather a driver of a sustainable digital age. The study used structured literature analysis and interviews with corporate best practices. The analysis and evaluation of the database follow the Hermeneutic Approach. Overall, this research led to the new aspects that underpin a convincing innovation scenario contributing to the broader use of digital methods and AI. With new findings, this study adds value to scientific literature and is evidence of the industry's leadership. Motivation/Background: The holistic approach from the perspective of a Civil Engineer, examining Construction 5.0, its related success factor and compass for socially sustainable construction and fulfillment of sustainability goals and ESG, may add value to your academic reading community. This manuscript is part of the author`s larger scientific research work “CDR in Construction in-line with ESG and SDGs”. Method: The study for this original article applies the so-called “Next Generation”-Method. It recognizes both challenges and limitations of digital transformation and the related human factors followed by normative questions. But it also deepens the holistic understanding of the explosive power and potential of new technologies such as AI catalyzing the construction branch into a more resilient, innovative one. Results: The aim of this work is to assess such an innovative scenario and ensure even wider adoption. The study critically questions whether the perception of the construction industry as one that is lagging behind digitization and AI is realistic or not, or whether the industry is rather a driver of a sustainable digital age. Conclusions: The paper´s discussion offers new aspects of this new scientific niche, to add value to scientific research. Furthermore, this paper aims to fully capture a new approach to assess the construction branch´s innovation strategy with a practicable framework for increasing both societal and corporate sustainability. The paper consists in a connection between a discovery, new scientific findings and its practical application.